Involvement of Teachers and Religious Leaders Working to Anticipate Ethical Decadence of Youth - Nurina (Lembaga KITA, 2022)
The problem of juvenile delinquency is today felt increasingly concerning by people in different parts of the world, both in developed and developing countries. This study took up the subject of study in the city of Sabang. Adolescent decadence is a period of decline in adolescent behavior in social life. A root cause of adolescent moral decadence is parental inattention in providing their children with education and religious instruction from an early age. As a result, the community environment no longer adequately supports children's morality, leading to the birth of moral decadence. The three factors that influence adolescent moral decay are family, school, and society. Parents play the most active role in the home, teachers are the second parent in schools, and religious leaders are the third parent in the community. Teachers and religious leaders as people who have a high enough charismatic are expected to be able to overcome the moral decadence of adolescents and have competence in preventing adolescent moral decadence through religious teachings, because it is with religious teachings that adolescent behavior can be well controlled as well as a motivator to carry out various positive activities. How is the cooperation of teachers and religious leaders in preventing adolescent moral decadence in the city of Sabang, because teachers and religious leaders are expected to be able to become partners with families and the government in preventing the moral decline of adolescents from spreading or increasing in number through various preventive measures to the fullest. Religious leaders as one who is responsible for providing non-formal religious education in the community, and religious teachers as providers of education in formal schools. The moral damage experienced by the Sabang youth has actually reached the stage of repair, because dirty talk, gambling, speeding have made them think it's normal. Preventive actions taken are by fostering good cooperation with families, businesses in schools in addition to providing religious education as well as a psychological-pedagogical approach, namely providing good examples to students, then business in the community by making religious activities.